ATP as a molecular mediator of the vascular response to injury - Guth, Christy M. (J Surg Res, 2017)
BACKGROUND: Human saphenous veins used for arterial bypass undergo stretch injury at the time of harvest and pre-implant preparation. Vascular injury promotes intimal hyperplasia, the leading cause of graft failure, but the molecular events leading to this response are largely unknown. This study investigated adenosine triphosphate (ATP) as a potential molecular mediator in the vascular response to stretch injury, and the downstream effects of the purinergic receptor, P2X7R, and p38 MAPK activation. MATERIALS AND METHODS: A subfailure stretch rat aorta model was employed to determine the effect of stretch injury on release of ATP and vasomotor responses. Stretch-injured tissues were treated with apyrase, the P2X7R antagonist, A438079, or the p38 MAPK inhibitor, SB203580, and subsequent contractile forces were measured using a muscle bath. An exogenous ATP (eATP) injury model was developed and the experiment repeated. Change in p38 MAPK phosphorylation after stretch and eATP tissue injury was determined using Western blotting. Non-injured tissue was incubated in the p38 MAPK activator, anisomycin, and subsequent contractile function and p38 MAPK phosphorylation were analyzed. RESULTS: Stretch injury was associated with release of ATP. Contractile function was decreased in tissue subjected to subfailure stretch, eATP, and anisomycin. Contractile function was restored by apyrase, P2X7R antagonism, and p38-MAPK inhibition. Stretch, eATP, and anisomycin-injured tissue demonstrated increased phosphorylation of p38 MAPK. CONCLUSIONS: Taken together these data suggest that the vascular response to stretch injury is associated with release of ATP and activation of the P2X7R/P38 MAPK pathway, resulting in contractile dysfunction. Modulation of this pathway in vein grafts after harvest and before implantation may reduce the vascular response to injury.